The role of socioeconomic background and prior achievement for students' perception of teacher support. Issue 7 (3rd October 2019) - Atlay, Cansu; Tieben, Nicole; Fauth, Benjamin; Hillmert, Steffen
Abstract: Building on the sociological work by Lareau, this study examined the association between students' socioeconomic background, prior achievement and the perception of teacher support within the classroom. We expected that students from higher socioeconomic backgrounds would be more critical about the support they receive in the classroom and rate their teachers more negatively, while those with higher prior achievement would perceive teacher support more positively. Multilevel models confirmed that there is a negative association between wealth and students' perception of two dimensions of teacher support, and a negative association between parental educational attainment and one dimension of teacher support. Our findings were in line with the 'sense of entitlement' theory by Lareau. Having higher prior achievement was associated with a more positive perception of teacher support, but did not seem to interact with socioeconomic background.